2021
DOI: 10.9734/afsj/2021/v20i530299
|View full text |Cite
|
Sign up to set email alerts
|

Oyster Mushroom (Pleurotus ostreatus) Cultivation Using Sawdust and Different Organic Manures

Abstract: Aims: The aim was to evaluate the performance of cultivating oyster mushroom (Pleurotus ostreatus) using sawdust and different organic manures.  Study Design: The experimental design used was the complete randomized design (CRD) and the Data obtained was subjected to Analysis of Variance (ANOVA) followed by Turkey’s Least Significant Difference(LSD) test to compare treatment means; differences was considered significant at 95% (P≤0.05) (SPSS Version 21 software). Place and Duration of Study: Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 3 publications
4
7
0
Order By: Relevance
“…P3 exhibited ash content of 2.1% while P6, P8, and P1 displayed 5.87%, 7.03%, and 9.14% of ash content, respectively. Our conclusions corroborated the data provided by [ 20 ] for Pleurotus species . According to recent studies [ 21 ], carbohydrate percentages typically range from 65.66 to 82.47%.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…P3 exhibited ash content of 2.1% while P6, P8, and P1 displayed 5.87%, 7.03%, and 9.14% of ash content, respectively. Our conclusions corroborated the data provided by [ 20 ] for Pleurotus species . According to recent studies [ 21 ], carbohydrate percentages typically range from 65.66 to 82.47%.…”
Section: Resultssupporting
confidence: 93%
“…In this study, we found that the contents of crude proteins, fats, carbohydrates, dietary fibers, total ash, and calorie values were in approximate ranges with each other and with the values as reported in previous studies. We concluded that the amounts of crude fats, total ash carbohydrates, proteins, dietary fibers, and calories in this study were within estimated ranges to one and also to the values reported in earlier studies [ 12 , 20 , 21 , 23 , 30 , 31 ]. These results might vary depending on the environmental conditions, substrate used, mushroom species, and drying techniques.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations